OC-080 Stat2 is a key mediator of acute pancreatitis. (17th June 2017) - Heath, H; Renney, G; Ward, M; Cutillas, P; Kudu, H; Goldin, R; Hutchins, R; Foster, GR; Brohi, K; Alazawi, W
Abstract : Introduction: Acute pancreatitis is a major cause of morbidity and mortality. It can be caused by a range of insults such as alcohol and gallstones which result in inappropriate activation of digestive enzymes, cellular injury, and local inflammation. The disease spectrum ranges from mild self-limiting illness through to systemic inflammation, organ dysfunction and death. Current predictive tools are crude, mostly due to a lack of understanding of the molecular mechanisms driving inflammation. For the same reasons, there are no specific therapies for acute pancreatitis and treatment is supportive. We have previously shown that the Stat2 protein is a pivotal mediator of TLR-mediated inflammation. Therefore, we tested the hypothesis that Stat2 mediates inflammation in mouse models and in patients with acute pancreatitis. Method: Wild type (WT) and Stat2 -/- mice were injected intraperitoneally with 2 µg or 1 µg cerulein hourly for 4 or 7 hours respectively; or 4 g/kg l-arginine. Pancreata and blood were harvested 1 hour and 24 hour after the final dose of cerulein, and 24 hour, 48 hour, 72 hour and 96 hour after l-arginine treatment. Blood was taken from patients with acute pancreatitis on the day of admission. PBMCs from patients and healthy controls were analysed by phos-flow following ex-vivo stimulation with interferon-α. Results: Stat2 -/- mice are protected in both cerulein and l-arginine models compared to WT, as evidenced by histology, significantly lower levels of serum amylase, inflammatory gene and protein expression and plasma leakage. Global protein expression analysis using label-free mass spectrometry identified 187 proteins whose expression was altered in cerulein-treated WT mice compared to control, 172 of which were differentially expressed in Stat2 -/- mice. Among these were major blood clotting pathways and we used rotational thromboelastometry to show that clotting abnormalities seen in WT cerulein-treated mice were more severe than in the protected Stat2-/-. Phosphoproteome analysis revealed differences in MAPK pathway proteins phosphorylation. Western blotting confirmed reduced NF-kB and phosphorylated p38MAPK in pancreatic nuclear extracts from Stat2 -/- compared to WT mice. In patients with acute pancreatitis, levels of activated STAT2 but not STAT1 were increased in PBMCs compared to healthy controls. Conclusion: Stat2 is a mediator of acute pancreatitis and required for MAPK and NF-kB function. Stat2 or associated factors identified in this study are potential biomarkers for pancreatic inflammation and/or therapeutic targets. Disclosure of Interest: None Declared